Review of Access Policy in the Credit Tranches and Under the Extended Fund Facility and the Poverty Reduction and Growth Facility, and Exceptional Access Policy. (Policy Papers; Policy Paper ;, 2008)
This paper reviews the Fund's access policy under its main financing facilities in the General Resources Account (GRA) and under the Poverty Reduction and Growth Facility (PRGF). It responds to the Board's request for a periodic review of the access policy, that is, the rules and practices that govern the amount of financing the Fund makes available to its members.